Effect of hydrostatic pressure on seed germination and subsequent growth of Silybum marianum (L.) Gaertn. seedlings in Middle Ural introduction - Sharova Elena; Kruglikov Nikolai; Belyaev Alexander (E3S Web of Conferences, 2023)
The influence of pre-sowing treatment of holy thistle seeds (Silybum marianum) by hydrostatic pressure (from 10 to 200 MPa) on the dynamics of the emergence of seedlings and the subsequent development of seedlings in the open ground in the Middle Urals has been studied. It is shown that the treatment of seeds with a pressure of 10 MPa during their subsequent sowing a day later (after drying) provided good germination and accelerated the passage of all stages of the ontogenesis of holy thistle plants in the dry growing season of 2021. At the same time, earlier and more friendly maturation of seeds was observed in comparison with the control group of plants. Under more favourable weather conditions in 2022, holy thistle seeds after the same pressure treatment (10MPa) and drying showed very good field germination (76%), a high rate of ontogenesis of seedlings similar to the reference and the best development of generative structures.